Impact of land use change on soil methane fluxes and diffusivity in Pampean plains, Argentina - De Bernardi, María; Priano, María Eugenia; Fernandez, María Elena; Gyenge, Javier; Juliarena, Maria Paula (Elsevier, 2023)
Upland soils are the main methane (CH4) biological sink, and may be affected by land-use change. Changes in land uses and soil management affect soil properties that control diffusion of gases, which in combination with microbial activity, determine CH4 flux (fCH4) through the soil. Net CH4 fluxes and diffusivity -estimated by the CH4 diffusion coefficient- were measured in three common land uses typical from Pampean plains, South America (natural grassland NG; Eucalyptus globulus Labill. afforestation E; and agricultural land AL: oat, soybean and red clover in successive cultivation) during two years (March 2017–March 2019). Methane fluxes in the soil-atmosphere interface were measured using the static chamber technique, and a diffusion model was applied to estimate soil CH4 diffusivity from soil porosity. We aimed to quantify the effect of land use change (both E and AL vs. NG, the reference system) on fCH4 and gas diffusivity due to changes in the soil parameters. Soils were net sinks in the three land uses, with mean CH4 flux higher in the afforestation, intermediate in the natural grassland and lower in the agricultural land (− 10.99 ± 5.85, − 8.9 ± 5.32 and − 4.58 ± 4.19 ng CH4 m−2 s−1, respectively). CH4 fluxes varied significantly through seasons and space coinciding with variations in water-filled pore space and air-filled pore space variables (ρ > 0.7 and <−0.7 respectively; p < 0.05). Land-use change metric for methane flux ΔfCH4 was − 2.1 ± 3.7 and 4.4 ± 2.5 for NG-E and NG-AL, respectively, indicating a significant increment in net CH4 uptake when the natural grassland is afforested and a decrease when it was converted to agricultural use. This change was mainly explained by changes in soil physical properties (bulk density, soil water content, WFPS and air filled porosity). In relation to this, soil CH4 diffusion coefficient followed the same pattern as fCH4 (0.024 ± 0.011; 0.015 ± 0.007 and 0.008 ± 0.007 cm2 s−1 for E, NG and AL respectively); and allowed us to recalculate mean CH4 fluxes. Theoretical and in situ measured CH4 fluxes were similar and followed the same patterns across land uses, suggesting the possibility to determine CH4 fluxes by means of simple measures of soil properties (bulk density and soil water content) and soil CH4 gradient concentration.